Little creeping things - Ichaso, Chelsea (2020)
Tormented by her guilt and classmate's taunts since she accidentally set a lethal fire as a child, Cassidy is implicated in her worst bully's murder and must find the killer before someone else dies.
Keywords: Murder -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Siblings -- Fiction; High schools -- Fiction; Schools -- Fiction; Mystery and detective stories